Hakikat Masyarakat Dalam Perspektif Filsafat Pendidikan Islam - Munthe, Hasanuddin; Usiono, Usiono (Al-Ulum: Jurnal Pendidikan Islam, 2024)
Humans are social creatures, meaning that fulfilling their needs requires help from others. As individuals relate to each other, the interactions that are built are a manifestation of human existence as social creatures. Society is a group of people who interact and are closely intertwined because they live in one area and have the same culture and identity. Apart from that, other social ties that create social interactions are the existence of certain systems, certain traditions, certain customs and certain laws. The methodology in this research is systematic review research sourced from published journals from 2018 to 2022. The research samples consist of journal publications on Google Scholar and Science Direct, consisting of 7 journals about the nature of society. The results of this research are that the essence of society in the philosophy of Islamic education refers to the nature or substance of society, including basic things about individuals, groups, or ummah, such as differences in views, the same goals, the same culture, and ways. and the same system of life. Working together to create patterns of mutual support. Pursuing common goals and certain targets within the framework of cooperation.